Decreased Functional Connectivity of Vermis-Ventral Prefrontal Cortex in Bipolar Disorder - Li, Huanhuan; Liu, Hu; Tang, Yanqing; Yan, Rongkai; Jiang, Xiaowei; Fan, Guoguang; Sun, Wenge (Frontiers in Human Neuroscience, 2021)
Objectives: To investigate changes in functional connectivity between the vermis and cerebral regions in the resting state among subjects with bipolar disorder (BD). Methods: Thirty participants with BD and 28 healthy controls (HC) underwent the resting state functional magnetic resonance imaging (fMRI). Resting-state functional connectivity (rsFC) of the anterior and posterior vermis was examined. For each participant, rsFC maps of the anterior and posterior vermis were computed and compared across the two groups. Results: rsFC between the whole vermis and ventral prefrontal cortex (VPFC) was significantly lower in the BD groups compared to the HC group, and rsFC between the anterior vermis and the middle cingulate cortex was likewise significantly decreased in the BD group. Limitations: 83.3% of the BD participants were taking medication at the time of the study. Our findings may in part be attributed to treatment differences because we did not examine the effects of medication on rsFC. Further, the mixed BD subtypes in our current study may have confounding effects influencing the results. Conclusions: These rsFC differences of vermis-VPFC between groups may contribute to the BD mood regulation.